Metastatic Squamous Cell Carcinoma of the Anus: Time for a Shift in the Treatment Paradigm?. (6th May 2012) - Dewdney, Alice; Rao, Sheela
Abstract : Anal cancers are rare tumours; however, the incidence is increasing in both men and women. Changing trends in sexual behaviour, smoking, and infection with the human papillomavirus are thought to be responsible for the increase. Patients with metastatic disease have a poor prognosis, with 5-year median overall survival rates of 10% in men and 20% in women. The standard systemic treatment of metastatic disease remains cisplatin and 5-fluorouracil, and aside from several non-randomised small phase II trials there has been no real progress over the past two decades. Based on the efficacy of cetuximab in squamous cell carcinomas from other primary sites, there appears to be clinical rationale for evaluation of anti-epidermal growth factor inhibitors in anal squamous cell carcinoma. In order to facilitate research and implement more effective treatment strategies international collaboration in clinical trials incorporating tissue collection for biomarkers is essential.